Inhibition of Enzymatic Browning and Oxidation in Pineapple Fruit by Different Thermal and Non-Thermal Techniques - Ahmed, Rana Fahad; Murad, Safoora; Shafiq, Laiba; Basharat, Shahrooz; Saeed, Khurram; Abid, Rabia; Ashfaq, Zareena; Waqar ul Hassan; Mazhar, Alishba (Indus Journal of Bioscience Research, 2025)
Pineapple (Ananas comosus L.) is a renowned tropical and subtropical fruit growing all around the world, having large nutritional and commercial values. Pineapple is greatly consumed in both ways, fresh and processed as dried pineapple, jam, jelly, juice, and dehydrated sweets. Pineapple has huge demand in food industry as it is rich in minerals, vitamins, antioxidants, and micronutrients, possessing many health benefits, such as improving digestion, lowering cholesterol, decreasing inflammation, ageing, and fighting cancer. A frequent issue that drastically influence the quality parameters of number of fruits and vegetables, is enzymatic browning. Enzymatic browning is the generation of dark pigment in fruit that doesn’t only change the color but also changes the texture and lowers the nutritional values and flavor of the product. To avoid the fall in quality standards of pineapple, proper inhibition of enzymatic browning is a need of hour. Based on the recent research, this review summarizes the thermal and non-thermal techniques in prevention of browning. The treatments effectively target the enzymes that catalysis the oxidation of phenolic like polyphenol oxidase (PPO) and pectin methylesterase (PME) that increase the availability of phenolics to PPO, ultimately causing the pigmentation (browning) in pineapple. The efficiency of treatments enhances by combining both thermal and non-thermal techniques, leading to greater suppression of enzymatic browning with hybrid treatments. Though, the gap between researchers, government officials, and industry stakeholders still needed to be addressed to cross the barriers about infrastructure, cost, and consumer acceptance.